Real time robustness test evaluation performance for intelligent fuzzy controller in extraction process - Z. M. Zakiah Mohd Yusoff; Nur Dalila Khirul Ashar; Zuraida Muhammad; Amar Faiz Zainal Abidin; Noor Fadzilah Razali; Shakira Azeehan Azli; A.M. MaArkom; Khairul Kamarudin Bin Hasan (Institute of Advanced Engineering and Science, 2019)
This paper presents the real time robustness test using intelligent fuzzy based controller in extraction process of essential oil is discussed in this study. Previous finding shows that the quality of the essential oil is affected by the steam temperature that acts as the control variable in this study. The robustness test is applied to the system during running process to show the system is robust to any operation conditions t make sure the controller is able to give a smooth control output response. The dynamic performance of the system are represented by applying standard performance criteria such as rise time Tr, settling time Ts, overshoot %OS, root mean square error (RMSE) and time on recovering load disturbance. Generally, the objectives in designing the controllers have been achieved because all intelligent fuzzy based controllers capable to regulate the desired set point by acting on the change in the output compared with the set point.